Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.4038/sljch.v32i1.737
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma and atopic symptoms in children aged 5-11years

Abstract: Objective To assess prevalence of asthma and atopic symptoms in a group of school children aged 5-11years and to look at prevalence of usage of asthma medications.Setting Three schools in Gampaha District in August 1998.Method A questionnaire translated into Sinhala was distributed to parents/guardians of 2195 children aged 5-11 years in Grades 1-5 of the schools and the filled questionnaires were collected through class teachers. Asthma, allergic rhinitis and eczema were defined using the clinical criteria of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 4 publications
0
12
1
Order By: Relevance
“…In our study, boys were found to have a higher frequency of rhinitis compared to girls, which is different to that reported by Fernando et al, who did not observe a significant gender difference for rhinitis [6]. Karunasekera et al [5] reported that they could not observe a significant difference for asthma between girls and boys, which is similar to our observation, while Fernando et al [6] reported a higher prevalence in boys. Overall, a male preponderance in allergic diseases has been observed worldwide [8][9][10][11].…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…In our study, boys were found to have a higher frequency of rhinitis compared to girls, which is different to that reported by Fernando et al, who did not observe a significant gender difference for rhinitis [6]. Karunasekera et al [5] reported that they could not observe a significant difference for asthma between girls and boys, which is similar to our observation, while Fernando et al [6] reported a higher prevalence in boys. Overall, a male preponderance in allergic diseases has been observed worldwide [8][9][10][11].…”
Section: Discussioncontrasting
confidence: 88%
“…Two studies have been conducted on childhood asthma and allergies in Sri Lanka using the ISAAC questionnaire [5,6]. The first, conducted over ten years ago, was restricted to Gampaha, one of 25 districts in the country [5]. The second, conducted 6 years ago, was restricted to the town of Chilaw in the North-Western Province [6].…”
Section: Introductionmentioning
confidence: 99%
“…Gampaha can be considered as a district with satisfactory health facilities and it is unlikely that an adolescent living with asthma, in Gampaha district would not have a diagnosis by a physician. The reported CA prevalence is lower compared to Karunasekara et al (2003) which showed an asthma prevalence of 23% and also to 17%, reported by Amarasekara et al (2010) [10,11]. It is important to note that the differences in case definitions used, age groups selected and sample selection could have influenced the disparity in results.…”
Section: Resultsmentioning
confidence: 63%
“…The questionnaire was in Sinhala (local dialect) and was pretested on a group of mothers of children with asthma attending the pediatric clinic. Restrictions in the preceding six months with regard to bathing, food (natural and commercial) and outdoor play activities (in children over 2 years) and school absenteeism (in children over 3 This study was conducted to ascertain the impact of inhaled corticosteroids therapy (ICS) in alleviation of lifestyle restrictions in 200 asthmatic children. 90 children on ICS were reviewed at 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…Although much interest has been directed towards its prevalence (2,3), risk factors(4) and therapeutic modalities(5-7), little has been studied about its impact on lifestyles of Sri Lankan children and their families. In clinical practice, it is an observation that parents impose restrictions on head baths, food and outdoor play activities.…”
mentioning
confidence: 99%